2019
DOI: 10.19127/mbsjohs.559446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Evaluation of Adnexal Torsion Patients in Adolescence, Reproductive and Postmenopausal Periods

Abstract: Objective: The objective of our study was to compare the adnexal torsion patients in different age groups clinically and pathologically. Methods: Sixty-eight patients who had applied with pelvic pain and adnexal torsion diagnosis had been confirmed intraoperatively were included in the study. Patients were divided into three groups based on their ages as the adolescent period (Group 1), reproductive period (Group 2) and postmenopausal period (Group 3). Ages, history of torsion, history of past operations, peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Ovarian torsion can occur in different periods of women's lives, including prepubertal, pubertal, reproductive, perimenopausal, and menopausal periods (11). Some studies have indicated that ovarian torsion is less common in the premenarchal age group and postmenopausal group (17.20%) (12). For instance, in a study including 53 torsion patients, the most common age range for torsion was found to be 20-29 years (13).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian torsion can occur in different periods of women's lives, including prepubertal, pubertal, reproductive, perimenopausal, and menopausal periods (11). Some studies have indicated that ovarian torsion is less common in the premenarchal age group and postmenopausal group (17.20%) (12). For instance, in a study including 53 torsion patients, the most common age range for torsion was found to be 20-29 years (13).…”
Section: Discussionmentioning
confidence: 99%